THE LINKAGE OF SUBSCRIPTION DECISIONS FROM SEVERAL FACTORS AT VIDEO ON-DEMAND STREAMING SERVICES IN JAKARTA CITY, INDONESIA - Handayani, Ellena Nurfazria; Quintania, Melani; Nova, Firsan; Aziizah, Kamiila (International Journal of Marketing Research Innovation, 2024)
The internet era and digital industry are increasingly benefiting from the increasing use of the internet in Asian countries. In the next few years, the existence of this video-on-demand streaming application will be increasingly popular among the public. This study aims to linkage between e-service quality and user experience impact on subscription decisions simultaneously and partially in Video On-Demand Streaming services in Jakarta City, Indonesia. This study uses a quantitative approach using multiple regression and causality type. Data collection from the period of March to June 2024 to participants at least 3 months and are at least 17 years old who subscribe to video-on-demand streaming services. Data procession with multiple regression analysis. This evidence supports based on proven empirical the Subscription Decisions from several factors, i.e., the significance of e-Service Quality and User Experience of Disney+ Hotstar Video On-Demand Streaming service application, with forty-six point eight percent both of them contributing components in this study. Hereafter, each of the e-Service Quality and User Experience factoring to influence the subscription decisions as partially at Video On-Demand Streaming Service of Disney+Hotstar as significantly. The study’s findings serve in-depth information for provider applications, especially in Indonesia to sustain by continuing to display film recommendations via the search icon and continuing to provide the latest films and series. This study recommended that understanding customer consumption patterns is important, as well as scheduling favorite films seasonally based on the amount of time spent on favorite genres/films and conducting surveys as often as possible with customers. JEL Classification Codes: C0, C83, M31, M37, N35.